Musakhkhir al-bilād : Tārīkh-i Shībāniyān - Qaṭaghān, Muḥammad Yār b. ʿArab, (Miras Maktoob, ISBN: 9789004365452., 2019)
ʿAbdallāh Khān b. Iskandar (d. 1006/1598) of the Uzbek Abu ʼl-Khayrid (Shībānid) dynasty was the ruler of the Khanate of Bukhara between 991/1583 and 1006/1598. Before then, he had already defended the territorial interests of his family against other branches of the Abu ʼl-Khayrids, putting his half-witted father on the throne in Bukhara in 961/1554 while he himself became the de facto ruler of the khanate, aged 23. During the time of ʿAbdallāh, Transoxania lived through a whole series of internal and external conflicts against a backdrop of ever changing alliances. In this period, ʿAbdallāh's centralizing policy led to considerable improvements in infrastructure, favouring the development of trade. The present work by Muḥammad Yār b. ʿArab Qaṭaghān is a history of the Abu ʼl-Khayrid dynasty with an emphasis on the reign of ʿAbdallāh Khān. Apart from its obvious historical interest, it contains a lot of linguistic and geographical information, besides highlighting the significance of Persianate culture in that region.